Efficient utilization of interparticle mesopores in aluminosilicate towards thermal energy storage. (April 2021) - Zhen, Liping; Meng, Genping; Zhou, Bo; Ma, Wenli; Yang, Yongjie; Duan, Xiaoya; Fu, Yilin; Wang, Huazhi
Highlights: A novel scaffold material, nano-aluminosilicate aggregates (n-ASA), with particle-agglomerated structure was prepared. n-ASA has a very high mesopore content of 98.3 % and a mesopore volume of 1.16 cm 3 /g. n-ASA/PEG composite with a PEG loading of 77.5 wt% and melting latent heat of 133.8 kJ/kg has been obtained. n-ASA/PEG composite exhibits excellent form and thermal stability. Abstract: Porous confinement, a method to prepare form-stable composite phase change materials (PCMs) by impregnating PCMs into the pores of porous scaffold materials, is proven to be an extraordinarily effective mean to address the leakage problem of PCMs during the phase transition process. For the energy storage capacities of composite PCMs are closely associated with the pore structure of scaffold materials, the research on the correlation between the structure of mesoporous scaffold materials and its loaded capability phase change materials is conducive to enriching the research system of heat storage materials. Herein, a novel form-stable composite PCM was fabricated successfully by integrating polyethylene glycol (PEG) into the mesopores of nano-aluminosilicate aggregates (n-ASA). The structure and the thermal properties of the samples were characterized. The results indicated that n-ASA had a self-sustaining microstructure by the aggregation of individual granules, and a very high mesopore content of 98.3 % and mesopore volume of 1.16 cm 3 /g. The maximum mass fraction of PEG loaded in the composite can reach up to 77.5 % and the melting latent heat of n-ASA/PEG were 133.8 J/g and 115.0 J/g, respectively. An increasement of 42.4 % in thermal conductivity of PEG was achieved after loading it into n-ASA with interconnected pores due to the provision of a faster heat transfer channel. Moreover, the thermal characteristics of n-ASA/PEG had no distinct change after 200 thermal cycles, indicating its prominent thermal reliability and stability. It is convinced that the mesopores of n-ASA are actually preferable over the micro- and macro-pores for holding PEG, and the synthesized n-ASA/PEG composite would be a prospective and potential candidate for low-temperature heat storage applications.